Rehabilitation: Mobility, Exercise and Sports - Woude, L.H.V. van der (IOS Press, 2013)
This book is a collection of summarized papers and poster presentations from the 4th International Congress Rehabilitation: Mobility, Exercise & Sports, which will be of interest to all those involved in the field of human movement sciences and the rehabilitation professions. Rehabilitation medicine is a relatively young discipline, as is the science of human movement, but both have progressed rapidly from their inception in the latter half of the 20th century to take their current place as important, multi-disciplinary, evidence based, academic and clinical research subjects. This congress, encompassing as it does the subject of assistive technology, brings together both local and international experts and practitioners for an exchange of current knowledge, experience and views, which will strengthen the collaboration between the rehabilitation profession and human movement and the social and engineering sciences worldwide. An individual’s mobility is crucial for function, participation and quality of life. Addressing questions such as rehabilitation diagnosis, treatment strategy and monitoring, as well as assistive technology and environmental optimization, the benefits of exercise and sport and the issues of risks for overuse and secondary impairment, this book is a major contribution to debate, knowledge provision and development in this important area.